Hubungan Ekspresi PD-L1 dengan Stadium Patologis dan Grading Karsinoma Urotelial Kandung Kemih - Addina, Rina (Majalah Kedokteran Andalas, 2024)
Objective: To determine the relationship between Programmed Cell Death-Ligand 1 (PD-L1) Â Â expression with histopathological variants, and staging of papillary thyroid carcinoma. Methods: This study is an observational research with a cross-sectional study. The sample consisted of papillary thyroid carcinoma cases from the Pathological Anatomy Laboratory of Dr. M. Djamil Padang General Hospital, spanning from January 2022 to December 2022, totaling 37 cases. Pathological stages of invasive urothelial carcinoma of bladder were assessed based on the TNM system WHO 2022 classification, and grades were evaluated according to the WHO 2022 classification. PD-L1 expression was assessed through immunohistochemical staining. Bivariate analysis was conducted using the Chi-square test, with statistical significance set at p < 0.05. Results: The study revealed a positive PD-L1 expression rate of 32.5%. Statistical analysis showed a significant association between PD-L1 expression and pathological stages of invasive urothelial carcinoma of bladder (p=0.019). High stages exhibited higher levels of PD-L1 expression. However, the study did not find a significant relationship between PD-L1 expression and grades of invasive urothelial carcinoma of bladder (p=0.152). Conclusion: There is an association between PD-L1 expression and pathological stages. PD-L1 expression is not associated with the grades of invasive urothelial carcinoma of bladder.